UNDERSTANDING PHONOLOGY: BASIC CONCEPTS AND EXAMPLES OF ANALYSIS - Nasywa Sakinah; Asti Ananta; Ajrul Khair; Yani Lubis (Rahis Cendekia Indonesia, 2025)
Studying the orderly arrangement and purpose of speech sounds in a language is essential to understanding phonology. Phonemes, the smallest units of sound that define meaning, are the subject of phonology, which also studies how these sounds are patterned and controlled by phonotactics, stress, and intonation. Phonology examines the abstract, conceptual representations of sounds and their language functions, in contrast to phonetics, which examines the physical production and acoustic characteristics of sounds. Identifying phonemes, their allophones (variations), and the principles that explain sound alterations in various contexts—such as assimilation and deletion—are all part of phonological analysis. The flap realization of /t/ and /d/ sounds between vowels and the pronunciation variants of the plural morpheme -s ([s], [z], [ɪz]) are two examples of English phonological rules. All things considered, phonology offers crucial information about how sounds work to transmit meaning and structure in language communication.